2013
DOI: 10.1155/2013/590190
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytokines in the Functional Activity of Phagocytes in Blood and Colostrum of Diabetic Mothers

Abstract: Immune response changes induced by diabetes are a risk factor for infections during pregnancy and may modify the development of the newborn's immune system. The present study analyzed colostrum and maternal and cord blood of diabetic women to determine (1) the levels of the cytokines IFN-γ and TGF-β and (2) phagocytic activity after incubation with cytokines. Methods. Colostrum and maternal and cord blood samples were classified into normoglycemic (N = 20) and diabetic (N = 19) groups. Cytokine levels, superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 35 publications
3
25
0
6
Order By: Relevance
“…Given its originality, it is difficult to compare this study with others. In a previous investigation, our research group identified the modulatory role of IFN-c and TGF-b in phagocytes from the maternal blood, cord blood, and colostrum of pregnant women with DM2 (25). Although many questions remain unanswered, the results of this study reinforce the importance of a rigid control of glycemic levels during pregnancy in order to maintain them within the normal range.…”
Section: Nd Mgh Gdm Dm2supporting
confidence: 62%
“…Given its originality, it is difficult to compare this study with others. In a previous investigation, our research group identified the modulatory role of IFN-c and TGF-b in phagocytes from the maternal blood, cord blood, and colostrum of pregnant women with DM2 (25). Although many questions remain unanswered, the results of this study reinforce the importance of a rigid control of glycemic levels during pregnancy in order to maintain them within the normal range.…”
Section: Nd Mgh Gdm Dm2supporting
confidence: 62%
“…Studies have related that this increase in microbicidal activity is crucial for the immune response of the host against intestinal amoebiasis [ 9 , 26 ]. The functional activity modulated by IFN-γ and TGF-β has also been reported for other infections [ 18 ].…”
Section: Discussionmentioning
confidence: 75%
“…Cytokine production may be associated with a number of processes such as alterations in intracellular Ca 2+ by phagocytes [ 18 ]. In the present study, TGF-β increased intracellular Ca 2+ release in MN cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations